Heat shock protein and antioxidant enzyme gene expression and fold changes in bone marrow samples from healthy rats - Walaa Mustafa; Ali Saeed Alchalabi (College of Education for Pure Sciences, 2022)
The hematopoiesis in the bone marrow in the early stages of life is very complex and involves many cellular factors under very strict micro-environments. The two important cellular factors are heat shock proteins and antioxidant enzymes. The aim of the study was to study the gene expression profile of healthy rats' bone marrow cells and niches particularly heat shock proteins and antioxidant genes. A total of thirty healthy Wister Albino rats at one, two, and three months old were involved throughout the study. Bone marrow samples were collected at a specified date according to the study design and utilized for qPCR test for expression of Hsps27, 90α, 90β, and antioxidant enzymes glutathione peroxidase1 (GPX1), catalase CAT and superoxide dismutase (SOD3) genes. The results revealed that there was a clear expression of both Hsps90α andβ in bone marrow cells throughout the study as well as the GPX1 gene. Furthermore, there was an increase in fold change of Hsps90α and β as well as GPX1, CAT, and SOD3 proteins as age progressed. In conclusion, hematopoietic cell differentiation and proliferation are regulated by bone marrow microenvironment stress conditions and by the expression of different Hsps and antioxidant genes. The protein folding process is a defense mechanism to protect the HSCs, and progenitors from un/misfolded proteins and to keep proteostasis.